The dynamics of cable bacteria colonization in surface sediments: a 2D view - Hang Yin (Nature Portfolio, 2021)
Abstract Cable bacteria that are capable of transporting electrons on centimeter scales have been found in a variety of sediment types, where their activity can strongly influence diagenetic reactions and elemental cycling. In this study, the patterns of spatial and temporal colonization of surficial sediment by cable bacteria were revealed in two-dimensions by planar pH and H2S optical sensors for the first time. The characteristic sediment surface pH maximum zones begin to develop from isolated micro-regions and spread horizontally within 5 days, with lateral spreading rates from 0.3 to ~ 1.2 cm day−1. Electrogenic anodic zones in the anoxic sediments are characterized by low pH, and the coupled pH minima also expand with time. H2S heterogeneities in accordance with electrogenic colonization are also observed. Cable bacteria cell abundance in oxic surface sediment (0–0.25 cm) kept almost constant during the colonization period; however, subsurface cell abundance apparently increased as electrogenic activity expanded across the entire surface. Changes in cell abundance are consistent with filament coiling and growth in the anodic zone (i.e., cathodic snorkels). The spreading mechanism for the sediment pH–H2S fingerprints and the cable bacteria abundance dynamics suggest that once favorable microenvironments are established, filamentous cable bacteria aggregate or locally activate electrogenic metabolism. Different development dynamics in otherwise similar sediment suggests that the accessibility of reductant (e.g., dissolved phase sulfide) is critical in controlling the growth of cable bacteria.